Knowledge, Attitudes and Environmental Tobacco Smoke Exposure Among Women Living in Elazığ City Center (Annals of Medical Research, 2021)
None
Keywords: s: Environmental Tobacco Smoke, Women, Knowledge, Attitude, Passive Smoking